Carotid artery stiffness in Behçet's disease - Yolbaş, Servet; Gozel, Nevzat; Dağlı, Mustafa Necati; Koca, Suleyman Serdar; Dönder, Emir (My University, 2017)
Objective: Increased carotid arterial stiffness (CAS) is a predictor of subclinical early atherosclerosis as well as carotid intima-media thickness (cIMT). We aimed to determine CAS and cIMT in Behçet's disease (BD).Material and Methods: BD (n=49) and rheumatoid arthritis (RA) (n=64) patients and healthy controls (HC) (n=40) were included in the study. cIMT was measured. CAS indices, including arterial compliance (AC), arterial distensibility (AD), Young's elastic modulus (YEM), Peterson's elastic modulus (Ep), and ? stiffness index (?SI) were measured based on the diameter-pressure relationship.Results: When compared to the HC group, the mean cIMT was significantly higher in the RA group (p=0.033), but it was not higher in the BD group. The CAS indices, including AD, AC, Ep, and ?SI were not significantly different among the study groups. Moreover, the cIMT and CAS indices were not significantly different between active (n=20) and inactive BD patients, and these indices were not correlated with the scores of disease activity. AD, AC and Ep were significantly lower in the BD patients with a positive pathergy reaction than in those with a negative reaction.Conclusion: These results suggest that BD does not directly lead to arterial stiffness or to an increase in cIMT.
Keywords: Genel ve Dahili Tıp